2021
DOI: 10.1371/journal.pone.0258575
|View full text |Cite
|
Sign up to set email alerts
|

Direct participation of people with communication disabilities in research on poverty and disabilities in low and middle income countries: A critical review

Abstract: Introduction An estimated 1 billion people with disabilities live in low and middle income countries, a population that includes people with communication disabilities (PwCD). PwCD are a heterogenous group with a wide range of abilities who may be underrepresented in research due to the communication demands involved in research participation. Methods A critical analysis of 145 studies from a previously published systematic review was undertaken with the aim of documenting the opportunities for direct partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Blasko et al (2022) identified in their meta‐analysis that research in disability disproportionately concerns high‐income countries, even though most people living with disability globally live in middle‐ and low‐income countries. Jagoe et al (2021) highlight that there are specific barriers to engaging people with disabilities in research in low‐income countries, which prevents the success of global efforts to reduce poverty. While these systematic reviews help to identify gaps in existing knowledge, both only included studies in English, demonstrating the urgent need for multi‐lingual research.…”
Section: Resultsmentioning
confidence: 99%
“…Blasko et al (2022) identified in their meta‐analysis that research in disability disproportionately concerns high‐income countries, even though most people living with disability globally live in middle‐ and low‐income countries. Jagoe et al (2021) highlight that there are specific barriers to engaging people with disabilities in research in low‐income countries, which prevents the success of global efforts to reduce poverty. While these systematic reviews help to identify gaps in existing knowledge, both only included studies in English, demonstrating the urgent need for multi‐lingual research.…”
Section: Resultsmentioning
confidence: 99%
“…However, the research productivity on poverty from disciplines, such as 'Dentistry', 'Decision Sciences', 'Nursing' and engineering disciplines was very low. This shows the need to scale up research productivity in these disciplines because research contributions enhance the holistic understanding of the poverty problem, which thus helps in informing evidence-based strategies needed for eliminating it [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of research investigating the needs of persons with different disability types 32 33. Future research should further explore the experiences that people with different disabilities have in various facets of their life; this will help guide effective strategising and programming by the government, NGOs and healthcare system.…”
Section: Discussionmentioning
confidence: 99%